Knowledge management orientation as a driver of competitive performance: Evidence from Polish SMEs in the aviation industry - Bogdan Wierzbiński; Piotr Zaborek; Małgorzata Wosiek; Tomasz Surmacz (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: This study aimed to investigate the role of knowledge management orientation (KMO) in small and medium-sized companies (SMEs) as a driver of competitive position, with customer orientation and participation in international networks as mediating variables. Research Design & Methods: The analysis involved structural equation modelling on a dataset of 281 SMEs from south-eastern Poland specializing in the aviation industry. Findings: The study found that KMO was the strongest positive determinant of the competitive position in the model, with more than half of the effect contributed by indirect regression paths involving mediator variables. Customer orientation enhanced competitive position only through direct effects, while international network involvement contributed to competitive advantage indirectly through the network benefits variable. Interestingly, the only meaningful difference between small and medium firms was found in the regression link between network benefits and competitive position, suggesting that larger firms are better equipped to translate benefits from cooperating with international supply chain partners into advantages against business rivals. Implications & Recommendations: To practitioners, the study demonstrates how the interplay between knowledge management and cooperation with the supply chain can provide substantive business advantages. Contribution & Value Added: The study adds to the existing theory by underscoring the importance of KMO to SMEs and explaining its role as an antecedent of beneficial cooperation within international networks of business partners.
Keywords: M15; L26; O32; 330; knowledge management orientation; internationalization; competitive performance; small and medium enterprises; intangible resources